An Analysis of The Influence of Foreign Direct Investment on Emerging Market Economies Growth - Jayadi, Akhmad; Prasetyo, Sigit Budi (Universitas Airlangga, 2022)
This study examines FDI influence on economic growth in 24 emerging market economies. The generalized Method of Moment (GMM) method is used in this research using panel data to see the effect of FDI on economic growth. This study also uses the Panel Vector Error Correction Model (PVECM) method to see the short-term relationship and Fully Modified Ordinary Least Square (FMOLS) to see the long-term relationship. This study finds strong empirical evidence indicating that the influence of FDI on economic growth is statistically significant in the short and long term. These results vary if we include the level of development reached by countries in emerging market economies. In upper-middle and lower-middle-income countries, FDI positively and greatly influences economic growth. Different results occur in high-income countries, and the results are positive and insignificant. The results show that FDI in high-income countries tends to leave these countries.